Empowerment and Improvement of Public Knowledge Through Education in An Effort to Stop the Spread of COVID-19 in Lok Baintan Village - Noor Amaliah (Borneo Community Development, 2021)
The incidence of Covid-19 in various countries is continuously increasing every day, the 2019 coronavirus outbreak (Covid-19) has created a global health crisis that has had a profound impact on the way we understand the world and our daily lives. Various efforts to prevent further spread have been made by the government in various countries, one of which is by providing education, education as a first step to form behaviors that can reduce the spread of Covid-19. However, there are still many people who are still negligent in paying attention to health protocols especially in this Normal EraNew. So that socialization and education are needed to improve public understanding of the importance of paying attention to health protocols in carrying out activities. The call to wear a mask and adhere to health protocols when doing activities outside the home is still ignored by some residents of Lok Baintan Village for various reasons. Educate about washing hands, maintaining distance, wearing masks when out of the house, and implementing health protocols wherever they are using educational videos. So it is expected to increase the knowledge and understanding of the community.